Nanoparticles: a promising tool against environmental stress in plants - Zhou, Xu; El-Sappah, Ahmed H.; Khaskhoussi, Amani; Huang, Qiulan; Atif, Amr M.; Elhamid, Mohamed A. Abd; Ihtisham, Muhammad; El-Maati, Mohamed F. Abo; Soaud, Salma A.; Tahri, Walid (Frontiers in Plant Science, 2025)
With a focus on plant tolerance to environmental challenges, nanotechnology has emerged as a potent instrument for assisting crops and boosting agricultural production in the face of a growing worldwide population. Nanoparticles (NPs) and plant systems may interact molecularly to change stress response, growth, and development. NPs may feed nutrients to plants, prevent plant diseases and pathogens, and detect and monitor trace components in soil by absorbing their signals. More excellent knowledge of the processes of NPs that help plants survive various stressors would aid in creating more long-term strategies to combat these challenges. Despite the many studies on NPs’ use in agriculture, we reviewed the various types of NPs and their anticipated molecular and metabolic effects upon entering plant cells. In addition, we discussed different applications of NPs against all environmental stresses. Lastly, we introduced agricultural NPs’ risks, difficulties, and prospects.